Penguatan Sikap Toleransi Mahasiswa Melalui Pendidikan Agama Islam Berperspektif Multikultural - Muhlar Muhlar; ST Wardah Hanafie Das (Institut Agama Islam Hidayatullah Batam, 2026)
Islamic Religious Education (PAI) of higher education has a strategic role in shaping the religious character as well as the social attitude of students in the midst of the reality of a multicultural society. This article aims to analyze the strengthening of student tolerance through Islamic Religious Education from a multicultural perspective. This study uses a qualitative literature review approach by examining journal articles, academic books, and relevant research reports published in the last five years. Data analysis is carried out through data reduction, thematic categorization, and conceptual synthesis. The results of the study show that the integration of multicultural values in PAI learning in higher education, through dialogical, contextual, and reflective approaches, contributes positively to strengthening student tolerance attitudes. his strengthening encourages students to understand diversity as a social reality as well as a value that is in harmony with Islamic teachings.